Genome-wide association study of copy number variation with lung function identifies a novel signal of association near BANP for forced vital capacity. Issue 1 (December 2016) - Shrine, Nick; Tobin, Martin; Schurmann, Claudia; Soler Artigas, María; Hui, Jennie; Lehtimäki, Terho; Raitakari, Olli; Pennell, Craig; Ang, Qi; Strachan, David; Homuth, Georg; Gläser, Sven; et al.
Abstract Background Genome-wide association studies of Single Nucleotide Polymorphisms (SNPs) have identified 55 SNPs associated with lung function. However, little is known about the effect of copy number variants (CNVs) on lung function, although CNVs represent a significant proportion of human genetic polymorphism. To assess the effect of CNVs on lung function quantitative traits, we measured copy number at 2788 previously characterised, common copy number variable regions in 6 independent cohorts (n = 24, 237) using intensity data from SNP genotyping experiments. We developed a pipeline for genome-wide association analysis and meta-analysis of CNV genotypes measured across multiple studies using SNP genotype array intensity data from different platform technologies. We then undertook cohort-level genome-wide association studies of CNV with lung function in a subset of 4 cohorts (n < =12, 403) with lung function measurements and meta-analysed the results. Follow-up was undertaken for CNVs which were well tagged by SNPs, in up to 146, 871 individuals. Results We generated robust copy number calls for 1962 out of 2788 (70 %) known CNV regions genome-wide, with 1103 measured with compatible class frequencies in at least 2 cohorts. We report a novel CNV association (discoveryP = 0.0007) with Forced Vital Capacity (FVC) downstream ofBANP on chromosome 16 that shows evidence of replication by a tag SNP in two independent studies (replicationP = 0.004). In addition, we provide suggestive evidence (discoveryP = 0.0002) for a role of complex copy number variation at a previously reported lung function locus, containing the rootletin geneCROCC, that is not tagged by SNPs. Conclusions We demonstrate how common CNV regions can be reliably and consistently called across cohorts, using an existing calling algorithm and rigorous quality control steps, using SNP genotyping array intensity data. Although many common biallelic CNV regions were well-tagged by common SNPs, we also identified associations with untagged mulitallelic CNV regions thereby illustrating the potential of our approach to identify some of the missing heritability of complex traits.